Students’ Perceptions of Teacher Talk in The Classroom Interaction to Enhance Students’ Motivation of Learning - Kamila, Dafina Shafa; Unsiah, Frida (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This current research aims to investigate students’ perceptions of the effect of teacher’s talk to enhance students’ motivation of learning. Therefore, the use of teacher talks focusing on praising and encouraging elements which is very useful in increasing student motivation. The participants were 93 students of the 8th grade in a public junior high school located in East Java Indonesia. The research design was quantitative approach. To collect the data, the researchers employed questionnaire as the instrument adapted from Ameiratrini & Kurniawan (2021), and Husna & Murtini (2019). The results show that the majority of the participants agree that receiving encouragement and praise from the teacher can increase students’ motivation to learn. It infers that encouragement and praise can encourage students’ participation.